2019
DOI: 10.9734/mrji/2019/v29i530173
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Kinetics of Microbial Consortium Isolated from Diesel Oil Impacted Soil in Delta Park, University of Port Harcourt, Nigeria

Abstract: Heavy-duty generators constitute a form of hydrocarbon pollution but enrich microorganisms to having degradative ability of hydrocarbons hence can be used for remediation. In this study a laboratory treatability (biodegradation screening) study was employed to investigate the hydrocarbon degradation competence of bacteria and fungi. Culture-dependent microbiological and physicochemical analyses was conducted on the soil samples obtained from the polluted site. The total aerobic heterotrophic bacterial and fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…have been reported in some articles to produce organic materials that possess biosurfactant or emulsification properties and thereby increasing the solubility and bioavailability of components for microbial activities (Effiong et al, 2019;Sampson et al, 2016). This study agrees strongly with the report of Udume et al (2019) who reported the preponderance of Bacillus spp and Pseudomonas sp from their separate investigations, especially spore formers. This further concretizes the report of Orji et al (2018) that microbes and their diversity correlate with the diversity of organic substances produced as a result of adaptation to the environmental fluxes.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…have been reported in some articles to produce organic materials that possess biosurfactant or emulsification properties and thereby increasing the solubility and bioavailability of components for microbial activities (Effiong et al, 2019;Sampson et al, 2016). This study agrees strongly with the report of Udume et al (2019) who reported the preponderance of Bacillus spp and Pseudomonas sp from their separate investigations, especially spore formers. This further concretizes the report of Orji et al (2018) that microbes and their diversity correlate with the diversity of organic substances produced as a result of adaptation to the environmental fluxes.…”
Section: Resultssupporting
confidence: 91%
“…These parameters are crucial in the monitoring of the environmental quality of a media especially in the interaction of exchangeable cations, while the temperature factor indicates the solubility of nutrients and formation of metal-oxide complexes (Orhohoro et al, 2018). Furthermore, Chima and Vure (2014) suggested that the pH and temperature indices of the soil were also related to the geochemical indices such as the soil pore-sizes, air-quality and permeability (Effiong et al, 2019). The concentration of Boron in the soil sample was 3.6 mg/kg; Mercury was 1.05mg/kg with the DPR target value of 0.30mg/kg and intervention value of 10mg/kg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation